Social Media as Online Shelter: Psychological Relief in COVID-19 Pandemic Diaries - Feng, Ran; Feng, Yulei; Ivanov, Alex (Frontiers in Psychology, 2022)
The pandemic diary on social media is a special form of online communication. Studying individual narratives in social network during the pandemic and post-pandemic period can help us generate valuable knowledge about the behaviors of media users and the function of social media in public health crisis. This research focuses on psychological relief in virtual public spaces, and explores how social media individual narratives affect people’s psychological health in the state of emergency from the perspective of narrative theory. Based on 19 in-depth interviews with Chinese diary writers, it has been found that the narrative genres of the pandemic diary were mainly Restitution and Quest narrative, while a few were categorized as “Restrained chaos” narrative. The purpose of editing pandemic diary is to communicate both inwardly and outwardly. The pandemic diary can promote self-relief, public communication, emotional drive, meaning connection and identity construction in public spaces, thus help shape a sense of unity and belonging, and facilitate psychological reconstruction of people who are vulnerable to potential mental health crises.